PERTANGGUNGJAWABAN NOTARIS TERHADAP PEMBUATAN AKTA BERITA ACARA RAPAT UMUM PEMEGANG SAHAM YANG TIDAK MEMENUHI KUORUM KEHADIRAN - Hamasah Ramadhani Hadid; Anriz Nazaruddin Halim; Amelia Nur Widyanti (Bajang Institute, 2025)
This study aims to analyze the notary's responsibility for making a deed of minutes of the General Meeting of Shareholders (GMS) that does not meet the attendance quorum. This research uses a juridical-normative research method with a statute approach, analysis approach, and case approach. The data is analyzed qualitatively by reviewing applicable legal regulations and related court decisions. This research uses 2 (two) theories, namely the theory of Legal Effects according to Soeroso and the theory of Responsibility according to Hans Kelsen. The legal problems discussed in this thesis are how the legal consequences of the deed of Minutes of the General Meeting of Shareholders that does not meet the attendance quorum made by the Notary and how the notary's responsibility for making the deed of Minutes of the General Meeting of Shareholders that does not meet the attendance quorum.The results showed that the making of a deed of GMS minutes without fulfilling the attendance quorum can lead to legal uncertainty and potentially harm shareholders. In addition, notaries as public officials making deeds have an obligation to ensure that every deed made is in accordance with applicable legal provisions, as stipulated in the Notary Position Law. Therefore, a deeper understanding is needed for notaries in carrying out their duties, as well as increased supervision and legal counseling to ensure legal certainty and protection for shareholders and avoid potential disputes in the future. The difference with previous studies is that this study specifically discusses the notary's responsibility for making the deed of minutes of the GMS that does not meet the attendance quorum, while other studies discuss the role of notaries in the GMS.